Prevalence and genomic characterization of Group A Streptococcus dysgalactiae subsp. equisimilis isolated from patients with invasive infections in Toyama prefecture, Japan. (6th December 2019) - Ishihara, Haruka; Ogura, Kohei; Miyoshi‐Akiyama, Tohru; Nakamura, Masahiko; Kaya, Hiroyasu; Okamoto, Shigefumi
Abstract: Streptococcus dysgalactiae subsp. equisimilis (SDSE) causes severe invasive streptococcal infections, especially in elderly people. Between 2013 and 2018, 88 streptococci were isolated from clinical blood culture in a hospital in Toyama prefecture, Japan. The collection included six Group A SDSE (ASD) strains, which are rarely isolated. Multilocus sequence typing categorized five of the six strains into ST128 and the remaining strain into a new type. Maximum‐likelihood phylogenetic analysis revealed that the six ASD strains had highly similar genome sequences. Bayesian analysis indicated that the most recent common ancestor of the strains appeared 39 years ago. The ASD strains possessed carbohydrate synthase genes that are conserved in Streptococcus pyogenes strains, whereas one strain featured a different arrangement of the gene cluster. The carbohydrate synthase genes varied by Lancefield type (A, C, and G).